+0  
 
0
55
1
avatar

3 cot^2(x) − 1 = 0

Guest Jun 1, 2017
Sort: 

1+0 Answers

 #1
avatar+75333 
+1

 

3 cot^2(x) − 1 = 0       add 1 to both sides

 

3 cot^2 (x)   =  1       divide both sides by 3

 

cot^2( x)  =   1/3       take the square root of both sides

 

cot (x)  =  ±√ (1/3)   = 

 

So

 

cot (x)  = √ (1/3)      and this happens at  pi/ 3   +  pi* n    where n is an integer

 

And

 

cot (x)  =  - √1/3)    and this   happens  at     -pi/3  +  pi*n   where n is an integer

 

 

 

cool cool cool

CPhill  Jun 1, 2017

9 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details